2022
DOI: 10.1038/s41467-022-33013-5
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting fidelity in mouse iPSCs depends on sex of donor cell and medium formulation

Abstract: Reprogramming of somatic cells into induced Pluripotent Stem Cells (iPSCs) is a major leap towards personalised approaches to disease modelling and cell-replacement therapies. However, we still lack the ability to fully control the epigenetic status of iPSCs, which is a major hurdle for their downstream applications. Epigenetic fidelity can be tracked by genomic imprinting, a phenomenon dependent on DNA methylation, which is frequently perturbed in iPSCs by yet unknown reasons. To try to understand the causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…4C). Likewise, the presence or absence of XIST, as well as the degree of erosion, does not affect methylation patterns at imprinted regions as depicted by IMPLICON, a targeted amplicon-seq-based method to measure DNA methylation at imprinted regions (Klobučar et al, 2020; Arez et al, 2022). IMPLICON was employed across two sets of isogenic XIST+ and XIST-hiPSCs, along the isogenic pair, CE and CD, exhibiting varying degrees of erosion.…”
Section: Resultsmentioning
confidence: 99%
“…4C). Likewise, the presence or absence of XIST, as well as the degree of erosion, does not affect methylation patterns at imprinted regions as depicted by IMPLICON, a targeted amplicon-seq-based method to measure DNA methylation at imprinted regions (Klobučar et al, 2020; Arez et al, 2022). IMPLICON was employed across two sets of isogenic XIST+ and XIST-hiPSCs, along the isogenic pair, CE and CD, exhibiting varying degrees of erosion.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, male and female pluripotent stem cells differ in autosomal gene expression as evident by transcriptomics analysis, albeit their comparable ground state of stemness ( Ronen and Benvenisty, 2014 ). Cellular sex difference is a key factor in dimorphic pathophysiology, which is caused by both sex hormones and chromosomal genotype ( Walker et al, 2021 ), as well as sex-dependent different regulations in genomic imprinting ( Arez et al, 2022 ). Some genes that were differentially expressed were sex-specific; for example, Zinc Finger Y-linked ( ZFY ) and Taxilin Gamma ( TXLNGY ) ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not examine the methylation levels at other ICRs. More recently, Arez et al have shown that the addition of ascorbic acid during the reprogramming of murine cells stabilizes the methylation of H19/Igf2 and Dlk1 - Dio3 regions which were hypermethylated without this addition [ 37 ]. Moreover, although it has long been accepted that hypoxia enhances the generation of iPSCs, its combination with ascorbic acid has never been reported [ 38 ].…”
Section: Discussionmentioning
confidence: 99%